Construction and Characterization of an Escherichia coli Strain Genetically Engineered for Ni(II) Bioaccumulation - Krishnaswamy, Rahul (American Society for Microbiology, 2000)
An Escherichia coli strain that accumulated Ni(II) was constructed by introducing the nixA gene (coding for a nickel transport system) from Helicobacter pylori into JM109 cells that expressed a glutathione S-transferase–pea metallothionein fusion protein. The resulting strain accumulated 15 μmol of Ni(II) per g (dry weight) from a 10 μM Ni(II) solution, four times the level taken up by JM109 cells. Ni(II) accumulation did not require an energy source, was inhibited by only 50% by 0.1 M NaCl, and occurred over the pH range from 3 to 9.